Explaining time changes in oral health-related quality of life in England: a decomposition analysis. Issue 12 (9th October 2017) - Tsakos, Georgios; Guarnizo-Herreño, Carol C; O'Connor, Rhiannon; Wildman, John; Steele, Jimmy G; Allen, Patrick Finbarr
Abstract : Background: Oral diseases are highly prevalent and impact on oral health-related quality of life (OHRQoL). However, time changes in OHRQoL have been scarcely investigated in the current context of general improvement in clinical oral health. This study aims to examine changes in OHRQoL between 1998 and 2009 among adults in England, and to analyse the contribution of demographics, socioeconomic characteristics and clinical oral health measures. Methods: Using data from two nationally representative surveys in England, we assessed changes in the Oral Health Impact Profile-14 (OHIP-14), in both the sample overall (n=12 027) and by quasi-cohorts. We calculated the prevalence and extent of oral impacts and summary OHIP-14 scores. An Oaxaca-Blinder type decomposition analysis was used to assess the contribution of demographics (age, gender, marital status), socioeconomic position (education, occupation) and clinical measures (presence of decay, number of missing teeth, having advanced periodontitis). Results: There were significant improvements in OHRQoL, predominantly among those that experienced oral impacts occasionally, but no difference in the proportion with frequent oral impacts. The decomposition model showed that 43% (–4.07/–9.47) of the decrease in prevalence of oral impacts reported occasionally or more often was accounted by the model explanatory variables. Improvements in clinical oral health and the effect of ageing itself accounted for most of the explained change in OHRQoL, but the effect of these factors varied substantially across the lifecourse and quasi-cohorts. Conclusions: These decomposition findings indicate that broader determinants could be primarily targeted to influence OHRQoL in different age groups or across different adult cohorts.